Milt-Egg Ratio in Artificial Fertilization of Pangasiid Catfish Injected by Gonadotropin Releasing Hormone-Analog (GnRH-a) and Domperidone Mixture - Subagja, J.; Sularto, .; Slembrouck, J. (Jurnal Akuakultur Indonesia, 2003)
Study on the level of gonadotropin hormone treatments combined with latency time to induce ovulation in Pangasius djambal was conducted in the Research Instalation of Germ Plasm, Cijeruk, Bogor. This study was carried out to investigate the effect of GnRH-a and domperidone mixture on the milt production and fertilization rates of Pangasius djambal, and to determine the optimal milt-egg ratio required for artificial fertilization. Different doses of hormone i.e: 0,3; 0,5 and 0,7 ml kg"1 body weight combined with latency time of 12, 24 and 48 h after inducing hormone were applied to increase milt-production. Milt dilution was 10"1, 10~2, 10"3, 10"4, 10"5, 10"6 and 10"7and evaluated for hatching rate and normality of larvae. The results showed that mean milt production was 4,3 ml/kg body weight, and there was interaction between hormone dose of 0,5 ml/kg of body weight and latency time 12 and 24 h that giving hatching rate of 77 to 83% ( p